The Effect of Harmonica Exercise on Inspiratory Capacity, Dyspnea, Exercise Capacity and Quality of Life of Chronic Obstructive Pulmonary Disease Patients - Angga M. Raharjo; Suradi Suradi; Jatu Aphridasari (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2019)
Background: Chronic inflammation in chronic obstructive pulmonary disease (COPD) causes respiratory muscle dysfunction and decreased respiratory muscle capacity. Incongruity of the capacity and the burden of the respiratory muscle results in increased symptoms of breathlessness, decreased inspiratory capacity, exercise capacity, and quality of life. The objectives of the study were to analyze the effect of harmonica exercise as a pulmonary rehabilitation modality on inspiratory capacity, shortness of breath symptoms, exercise capacity, and quality of life on stable COPD patient. Methods: Clinical trials with pre and post test group design were performed on 30 stable COPD patients at the respiratoy clinic at Dr. Moewardi Hospital Surakarta in August - September 2017 taken by purposive sampling. Evaluation of inspiratory capacity (IC) by spirometry, symptoms of breathlessness by mMRC, exercise capacity by 6MWT and quality of life by SGRQ were measured at baseline and after 6 weeks in the harmonic and control exercises group. Results: A total 30 stable COPD subjects met criteria and divided into two groups. The harmonica training group increased IC (1.78±0.30 litre) and 6MWT (420.00±35.49 meters), decreased mMRC score (1.00±0.458) and SGRQ score (33.87±6.05) after exercise were had significant differences (p